A projektmenedzsment szervezeti háttere - Keczer, Gabriella (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
One of the key conditions of successful project management is finding the most effective organizational solution. A project can be managed either in our organization (in functional or matrix structure, or by creating an individual project unit), or we can contract with another company. In my paper I summarize and evaluate these organizational solutions on the basis of its literature, and I present a case study: the organizational background of an environmental infrastructure development project in Szeged.